Taguchi-Assisted of Ligninase Production by Phanerochaete chrysosporium ITB Isolate Biofilm - Mutmainah, Siti; Wahab, Roswanira Abdul; Sanjaya, Eli Hendrik; Susanti, Evi (Universitas Gadjah Mada, 2025)
The Phanerochaete chrysosporium ITB isolate can form a biofilm when grown on a support material, in which the attached cells are in a sessile state, which allows the cells to thrive better compared to other conditions. This study uses the Taguchi model to explore the ligninase (LiP, MnP, and laccase) production by P. chrysosporium ITB isolates immobilized on polypropylene (PP). This research was carried out in a laboratory experimental manner, which consisted of stages that included the preparation of spore suspension and optimization of conditions for the production of ligninase using Taguchi. The results showed that lignin peroxidase (LiP) and laccase (420.1 and 78.69 U/mg) enzymes were optimally produced using an inoculum size of 5 × 103 spore/mL, with a growth duration of 6 d at pH 3 and required 0.4 g/mL of PP to yield a 0.36% biofilm weight. The optimal production of MnP (410.23 U/mg) warranted an inoculum size of 5 × 102 spore/mL with incubation of 4 d at pH 5, and immobilization on 0.20 g/mL PP, to give a final biofilm weight of 0.09%. These results indicate a potential LiP and laccase production by the biofilm of P. chrysosporium on the polypropylene as supporting materials.